2010
DOI: 10.1128/aac.01649-09
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Doripenem Based on Data from Phase 1 Studies with Healthy Volunteers and Phase 2 and 3 Studies with Critically Ill Patients

Abstract: A population pharmacokinetic model of doripenem was constructed using data pooled from phase 1, 2, and 3 studies utilizing nonlinear mixed effects modeling. A 2-compartment model with zero-order input and first-order elimination best described the log-transformed concentration-versus-time profile of doripenem. The model was parameterized in terms of total clearance (CL), central volume of distribution (V c ), peripheral volume of distribution (V p ), and distribution clearance between the central and periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 21 publications
6
59
7
Order By: Relevance
“…Thus, the variation in PK/PD breakpoints may be caused by a subtle difference in population. Secondly, the population PK model established by Nandy et al 15) was developed in non-Japanese subjects, which may contribute to the difference between the PK/PD breakpoint observed in this study and the PK/PD breakpoint reported previously. However, the population mean parameters estimated using a previously reported population PK model for Japanese subjects 21) were comparable to those estimated by the population PK model reported by Nandy et al 15) Hence, the difference in ethnicity in the development of two population PK models established by Nandy et al or Ikawa et al may have little influence on our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the variation in PK/PD breakpoints may be caused by a subtle difference in population. Secondly, the population PK model established by Nandy et al 15) was developed in non-Japanese subjects, which may contribute to the difference between the PK/PD breakpoint observed in this study and the PK/PD breakpoint reported previously. However, the population mean parameters estimated using a previously reported population PK model for Japanese subjects 21) were comparable to those estimated by the population PK model reported by Nandy et al 15) Hence, the difference in ethnicity in the development of two population PK models established by Nandy et al or Ikawa et al may have little influence on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as DRPM was administered as empirical therapy for conditions without clearly identified pathogens, a few patients were likely to have no infection. Taken the above factors into consideration, we selected the model reported by Nandy et al 15) as the population PK model to implement Bayesian estimate in our study. In addition, in order to make predicted concentration profile more concrete, Bayesian estimate was implemented using five observed concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median blood, dialysate and replacement fluid rates were 200, 1000 and 1000 mL/h, respectively. The mean value for total doripenem clearance was 4.46 L/h (normal range: ½ to 16 L/h, [22]) and volume of distribution was 0.63 L/kg BW (normal range: 0.23 to 0.35 L/kg BW, [22]). Doripenem elimination by CHDF depended on the rate filtration and contributed from 30% to 37% of total clearance.…”
Section: Carbapenum (Doripenem; Meropenem)mentioning
confidence: 99%